Religious Identity and National Conflict in the 20th Century Indonesia - Jonathan, Andreas (DINIKA : Academic Journal of Islamic Studies, 2017)
This study attempts to discuss on how religious identities contribute to or was in conflict with the emerging national identities, with focusing issue on the struggle of Islam in its relation to Indonesian identity as a multi-religious nation and Pancasila state. Based on the critical analysis from the various literature, the result of the study showed that Islam did both contribute and was in conflict with the Indonesian national identity. The Islamist fights for the Islamic state, the nationalist defends Pancasila state. As long as Islam is the majority in Indonesia and as long as there is diversity in Islam, especially in the interpretation of Islam and the state, Indonesian national identity will always be in conflict between Pancasila state and Islamic state. Even though, the role of religion in society and nation change is very significant. The Islamist is always there, although it is not always permanent in certain organizations. In the past, NU and Muhammadiyah were considered as Islamist, but today they are nationalist. At the same time, new Islamist organizations and parties emerge to continue their Islamist spirit.